World view as a theological-hermeneutical premise in the interpretation of the Old Testament with particular reference to the Reformed Church in Zambia - Zulu, Edwin (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 1996.